Vascular Contractility Relies on Integrity of Progranulin Pathway: Insights Into Mitochondrial Function - Shubhnita Singh; Ariane Bruder; Rafael M. Costa; Juliano V. Alves; Sivakama Bharathi; Eric S. Goetzman; Thiago Bruder‐Nascimento (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The complex interplay between vascular contractility and mitochondrial function is central to cardiovascular disease. The progranulin gene (GRN) encodes glycoprotein PGRN (progranulin), a ubiquitous molecule with known anti‐inflammatory property. However, the role of PGRN in cardiovascular disease remains undefined. In this study, we sought to dissect the significance of PGRN in the regulation vascular contractility and investigate the interface between PGRN and mitochondrial quality. Methods and Results We used aortae from male and female C57BL6/J wild‐type (PGRN+/+) and B6(Cg)‐Grntm1.1Aidi/J (PGRN−/−) mice. Our results showed suppression of contractile activity in PGRN−/−, followed by reduced α‐smooth muscle actin expression. Mechanistically, PGRN deficiency suppressed mitochondrial respiration, induced mitochondrial fission, and disturbed autophagy process and redox signaling, while restoration of PGRN levels in aortae from PGRN−/− mice via lentivirus delivery ameliorated contractility and boosted mitochondria activity. In addition, in vivo treatment with mitochondrial fission inhibitor restored mitochondrial quality and vascular contractility, while vascular smooth muscle cells overexpressing PGRN displayed higher lysosome biogenesis, accelerated mitophagy flux, and mitochondrial respiration accompanied by vascular hypercontractility. Finally, angiotensin II failed to induce vascular contractility in PGRN−/−, suggesting a key role of PGRN to maintain the vascular tone. Conclusions Our findings suggest that PGRN preserves the vascular contractility via regulating mitophagy flux, mitochondrial activity and dynamics, and redox signaling. Therefore, loss of PGRN function appears as a pivotal risk factor in cardiovascular disease.